Metode Harumpala: Strategi Pembelajaran Untuk Membantu Siswa SD 101774 Sampali Mengingat Rumus Matematika Dengan Mudah - Ade Vilya Ramadhani; Ananda Tampubolon; Dwi Tarisya; Meyliana Perwita Saragih; Wulandari Wulandari; Nurhudayah Manjani (Pusat Riset dan Inovasi Nasional, 2024)
Learning mathematics in elementary school is often labeled as a difficult and scary subject by students. This assumption can lead to suggestions to students that this subject is difficult to learn. This research aims to overcome the problem of difficulties in understanding and remembering mathematical formulas at SDN 101774 Up, especially in high classes by using a fun learning method, namely HARUMPALA (Memorizing Formulas Using Songs). This approach converts mathematical formulas into familiar children's song lyrics, making it easier for students to remember and understand the formulas. This research uses a qualitative approach with interview methods and literature review to gain an in-depth understanding of the factors that cause difficulties in learning mathematics at SDN 101774 Till. The research results show that the HARUMPALA method is effective in reducing mathematics anxiety and increasing students' ability to remember formulas. With a more enjoyable learning atmosphere, it is easier for students to understand and apply mathematical concepts in more depth. This method not only helps in memorizing formulas, but also in understanding the concept and its application.